2010
DOI: 10.1186/1471-2407-10-179
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of resistance in SR/CR mice: the critical role of chemoattraction in the cancer/leukocyte interaction

Abstract: BackgroundSpontaneous regression/complete resistance (SR/CR) mice are a unique colony of mice that possess an inheritable, natural cancer resistance mediated primarily by innate cellular immunity. This resistance is effective against sarcoma 180 (S180) at exceptionally high doses and these mice remain healthy.MethodsIn this study, we challenged SR/CR mice with additional lethal transplantable mouse cancer cell lines to determine their resistance spectrum. The ability of these transplantable cancer cell lines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…On the other hand, such experimental results cast a certain doubt to the robustness of the SR/CR mouse model as a general cancer resistance model. Taken together, we conclude that innate immune cells from SR/CR cancer resistant mice seem to be functionally different from those from nonresistant controls and [14], and the restricted cancer resistance mechanism of SR/CR mice in the present experimental context appeared to be dependent on interactions between S180 cells and SR/CR leukocytes. The data substantiate that growth and spread of cancer cells are dependent on a complex interplay between the cancer cells and the host organism.…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, such experimental results cast a certain doubt to the robustness of the SR/CR mouse model as a general cancer resistance model. Taken together, we conclude that innate immune cells from SR/CR cancer resistant mice seem to be functionally different from those from nonresistant controls and [14], and the restricted cancer resistance mechanism of SR/CR mice in the present experimental context appeared to be dependent on interactions between S180 cells and SR/CR leukocytes. The data substantiate that growth and spread of cancer cells are dependent on a complex interplay between the cancer cells and the host organism.…”
Section: Discussionmentioning
confidence: 50%
“…57 One study has shown that increased direct contact between tumor cells and PMN plus macrophages in mice is responsible for resisting lethal doses of cancer cells. 70, 71 However, the molecular mechanism for such efficacy remains unclear.…”
Section: Direct Cancer and Innate Immune System Interactionsmentioning
confidence: 99%
“…Studies on a mouse colony that show spontaneous regression of tumors and cancer resistance reveal that tumor regression requires both the infiltration of tumors with leukocytes, particularly PMNs, and the recognition of some undetermined surface markers on tumor cells [97]. …”
Section: Targeting Tumor-host Interactionmentioning
confidence: 99%